Improved mechanical and ultraviolet shielding performances of hydroxyethyl cellulose film by using aramid nanofibers as additives. (1st March 2021) - Huang, Jizhen; Lu, Zhaoqing; Li, Jiaoyang; Ning, Doudou; Jin, Zhanfan; Ma, Qin; Hua, Li; E, Songfeng; Zhang, Meiyun
Graphical abstract: Highlights: Aramid nanofibers can be used as a multifunctional nano-additive. The tensile strength of hydroxyethyl cellulose can be improved by aramid nanofibers. Aramid nanofibers can enhance the ultraviolet shielding of hydroxyethyl cellulose. Abstract: Recently, aramid nanofibers (ANFs) have drawn the attention of scientist due to the high mechanical strength, high-temperature resistance, and high electrical and thermal insulation properties. In this work, we aimed at improving the mechanical and ultraviolet shielding properties of hydroxyethyl cellulose (HEC) film by using ANFs as additives. Mechanical results show that the 1.0 % ANFs could improve the tensile strength of pure HEC film by 176.6 %. Meanwhile, the ANFs additives can also enable the HEC film excellent ultraviolet (UV) shielding and visible light transmittance, as well as high UV radiation resistance ability. It is believed that the high mechanical strength of the HEC/ANFs composites is derived from the rearrangement of HEC chains along the tensile direction after the addition of hard ANFs and the enhanced hydrogen bonds between HEC and ANFs.